UMA VIAGEM POR IBIAMORÉ, O TREM FANTASMA - Salomon, Valéria Brisolara (Organon, 2003)
This text invites the reader to set off on a journey throughIbiamoré, o trem fantasma, a novel by Roberto B. Martins. This trajectorydoes not aim at the finish line, at exhausting the novel, but at taking one,among the many possible ways along the novel, which I hope will opendoors to many journeys to come. Nevertheless, in order to accomplish thistravel, it is necessary that we stop at some stations and speak of some ofthe many passengers of this train that all of us will once take: the train ofthe night or the train of death.